2012
DOI: 10.4103/2153-3539.104905
|View full text |Cite
|
Sign up to set email alerts
|

Mouse cursor movement and eye tracking data as an indicator of pathologists' attention when viewing digital whole slide images

Abstract: Context:Digital pathology has the potential to dramatically alter the way pathologists work, yet little is known about pathologists’ viewing behavior while interpreting digital whole slide images. While tracking pathologist eye movements when viewing digital slides may be the most direct method of capturing pathologists’ viewing strategies, this technique is cumbersome and technically challenging to use in remote settings. Tracking pathologist mouse cursor movements may serve as a practical method of studying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Participants were divided into three groups [25][27]: 1) Novices were comprised of current residents with limited breast pathology experience (n = 3); 2) Intermediates were comprised of faculty members specializing in dermatopathology and general anatomic pathology (n = 2), and 3) Experts were comprised of faculty who specialized in breast pathology (n = 2).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were divided into three groups [25][27]: 1) Novices were comprised of current residents with limited breast pathology experience (n = 3); 2) Intermediates were comprised of faculty members specializing in dermatopathology and general anatomic pathology (n = 2), and 3) Experts were comprised of faculty who specialized in breast pathology (n = 2).…”
Section: Methodsmentioning
confidence: 99%
“…Web server [42,43] Tracking pathologists' behavior Eye tracking [44], mouse tracking [45] and viewport tracking [46] Active learning Uncertainly sampling [43], Query-by-Committee [47], variance reduction [48] and hypothesis space reduction [49] Multiple instance learning Boosting-based [50,51], deep weak supervision [52] and structured support vector machines (SVM) [53] Semi-supervised learning Manifold learning [30] and SVM [54] Transfer learning Feature extraction [55], fine-tuning [16,56,57]…”
Section: Gui Toolsmentioning
confidence: 99%
“…Another interesting idea to reduce working time is to automatically localize ROIs during diagnosis, which uses the usual working time for diagnosis as labeling by tracking pathologists' behavior. This approach tracks pathologists' eye movement [44], mouse cursor positions [45] and change in viewport [46]. However, localizing ROIs accurately from these tracking data is not always easy since pathologist's do not always spend time looking at ROIs, and boundary information obtained by these approaches tends to be less clear.…”
Section: Insufficient Labeled Imagesmentioning
confidence: 99%
“…The software-based tracking method for WSIs appeared to be a good choice for the exam session environment. This approach has certain advantages over solutions described in [ 9 , 11 ], which involve eye movement tracking. Once implemented on a WSI software platform, our method is easy to adapt and requires no changes in the way how WSIs are normally viewed.…”
Section: Discussionmentioning
confidence: 99%
“…Using a software method is an alternative. It has already been suggested that signals collected from regular WSI viewing hardware, like mouse cursor position [ 11 ] and data from slide navigation [ 12 ], may have potential in identification of viewing behavior.…”
Section: Introductionmentioning
confidence: 99%